Risk Factors for Small Bowel Obstruction After Laparoscopic Ileal Pouch–Anal Anastomosis for Inflammatory Bowel Disease: A Multivariate Analysis in Four Expert Centres in Europe. (11th October 2018) - Mege, D; Colombo, F; Stellingwerf, M E; Germain, A; Maggiori, L; Foschi, D; Buskens, C J; de Buck van Overstraeten, A; Sampietro, G; D'Hoore, A; Bemelman, W; Panis, Y
Abstract: Background and Aims: Although laparoscopy is associated with a reduction in adhesions, no data are available about the risk factors for small bowel obstruction [SBO] after laparoscopic ileal pouch–anal anastomosis [IPAA]. Our aims here were to identify the risk factors for SBO after laparoscopic IPAA for inflammatory bowel disease [IBD]. Methods: All consecutive patients undergoing laparoscopic IPAA for IBD in four European expert centres were included and divided into Groups A [SBO during follow-up] and B [no SBO]. Results: From 2005 to 2015, SBO occurred in 41/521 patients [Group A; 8%]. Two-stage IPAA was more frequently complicated by SBO than 3- and modified 2-stage IPAA [12% vs 7% and 4%, p = 0.04]. After multivariate analysis, postoperative morbidity (odds ratio [OR] = 3, 95% confidence interval [CI] = 1.5–7, p = 0.002), stoma-related complications [OR = 3, 95% CI = 1–6, p = 0.03] and long-term incisional hernia [OR = 6, 95% CI = 2–18, p = 0.003] were predictive factors for SBO, while subtotal colectomy as first surgery was an independent protective factor [OR = 0.4, 95% CI = 0.2–0.8, p = 0.002]. In the subgroup of patients receiving restorative proctocolectomy as first operation, stoma-related or other surgical complications and long-term incisional hernia were predictive of SBO. In the patient subgroup of subtotal colectomy as first operation, postoperative morbidity and long-term incisional hernia were predictive of SBO, whereas ulcerative colitis and a laparoscopic approach during the second surgical stage were protective factors. Conclusions: We found that SBO occurred in less than 10% of patients after laparoscopic IPAA. The study also suggested that modified 2-stage IPAA could potentially be safer than procedures with temporary ileostomy [2- and 3-stage IPAA] in terms of SBO occurrence.